2009
DOI: 10.1007/s12519-009-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum total and free carnitine levels in children with asthma

Abstract: Serum carnitine levels decrease in children with moderate asthma during exacerbation of asthma and shortly thereafter. Further studies are needed to evaluate the effect of carnitine treatment on serum carnitine level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…These findings agreed with the results of Asilsoy et al who found that serum carnitine levels were decreased in children with moderate asthma during exacerbation of asthma and shortly thereafter [13]. Whether the decrease in serum carnitine in children with moderate persistent asthma is a cause or an effect, needs to be further studied.…”
Section: Discussionsupporting
confidence: 91%
“…These findings agreed with the results of Asilsoy et al who found that serum carnitine levels were decreased in children with moderate asthma during exacerbation of asthma and shortly thereafter [13]. Whether the decrease in serum carnitine in children with moderate persistent asthma is a cause or an effect, needs to be further studied.…”
Section: Discussionsupporting
confidence: 91%
“…In the examination of metabolome module‐asthma link, there were no individual but integrated relationships (eg, the nasopharyngeal‐carnitine module). In agreement with our finding, studies have revealed the role of carnitines in childhood respiratory diseases and asthma 46‐49 . For example, circulating carnitine levels have been reported to be decreased in newborns with respiratory distress syndrome 46 and in children with recurrent pulmonary infections 47 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, higher carnitine and phenylalanine were detected in asthma patients [44, 45]. The level of acetylcarnitine and valine were also significantly increased in ovalbumin (OVA)-induced asthma model [46], which are consistent with our results.…”
Section: Discussionsupporting
confidence: 89%